Bridged and superbridged cyclopropenylidene iminium salts - Schuster-Haberhauer, Andreea; Rominger, Frank; Gleiter, Rolf (Tetrahedron letters, 1999)
The reaction of bridged cyclopropenones and doubly bridged biscyclopropenones with triethyloxonium fluoroborate and an amine led to the tetrafluoroborates of bridged and superbridged cyclopropenylidene iminium salts.
Gesehen am 13.11.2020